Analysis of Factor Affecting MSME Performance in Medan Petisah District, Medan City - Ryan Oka Wijaya; Winda Doloksaribu; Jerome Karsten Yapin; Albert (JURNAL COMPUTECH & BISNIS, 2026)
This study examines the determinants of the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan Petisah District, Medan City. The independent variables analyzed include digital marketing (X1), price (X2), and service quality (X3), whereas MSME performance (Y) functions as the dependent variable. A quantitative research methodology was utilized with 100 respondents chosen by chance sampling. Data were gathered using surveys and processed with Structural Equation Modeling – Partial Least Squares (SEM-PLS). The findings demonstrate that digital marketing has a positive and significant impact on MSME performance (t-statistic = 4.215; p = 0.000), while pricing also has a positive and significant impact (t-statistic = 3.233; p = 0.001). In contrast, service quality does not exhibit a significant effect (t-statistic = 1.693; p = 0.090). All three variables concurrently exert a positive and significant influence on MSME performance, evidenced by an F-value of 22.9 and an Adjusted R-Square of 32.3%.